2006
DOI: 10.1086/499526
|View full text |Cite
|
Sign up to set email alerts
|

Proper Motions of Dwarf Spheroidal Galaxies fromHubble Space TelescopeImaging. IV. Measurement for Sculptor

Abstract: This article presents a measurement of the proper motion of the Sculptor dwarf spheroidal galaxy determined from images taken with the Hubble Space Telescope using the Space Telescope Imaging Spectrograph in the imaging mode. Each of two distinct fields contains a quasi-stellar object which serves as the "reference point." The measured proper motion of Sculptor, expressed in the equatorial coordinate system, is (µ α , µ δ ) = (9 ± 13, 2 ± 13) mas century −1 . Removing the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(137 citation statements)
references
References 46 publications
6
129
2
Order By: Relevance
“…In the case of Sculptor, a similar orbital study was carried out by Piatek et al (2006). They obtain 95% confidence intervals on perigalacticon and apogalacticon of 31 < rp < 83 kpc and 97 < ra < 313 kpc, implying 0.26 < e < 0.60 with the Galactic potential model from Johnston et al (1995).…”
Section: Orbital Motionsmentioning
confidence: 81%
“…In the case of Sculptor, a similar orbital study was carried out by Piatek et al (2006). They obtain 95% confidence intervals on perigalacticon and apogalacticon of 31 < rp < 83 kpc and 97 < ra < 313 kpc, implying 0.26 < e < 0.60 with the Galactic potential model from Johnston et al (1995).…”
Section: Orbital Motionsmentioning
confidence: 81%
“…Right column: Individual pdfs marginalised over the other two components. The measurements from Piatek et al (2006) are shown in red, while those by Schweitzer et al (1995) are shown in blue. The vertical lines in the right panels and the dot in the left panels indicate the maximum likelihood values.…”
Section: Appendix B: Centre Of Mass Velocity Of Sculptormentioning
confidence: 99%
“…The Carina dSph was discovered in 1977 [7]. The best estimates of the orbits of the two dSphs show that Carina is likely to be more tidally disrupted than Sculptor [8,9], leading to higher uncertainties for the DM content of the Carina dSph than of the Sculptor.…”
Section: Introductionmentioning
confidence: 99%